Promoción y prevención en salud oral en niños de preescolar y representantes legales del colegio INEM sede Ciudad Jardín - Hernández Peñaranda, Laura Valentina; Pulgarin Saravia, Marly Janeth (Universidad Antonio Nariño, 2023)
Strengthen the promotion and prevention of oral health in preschool children and legal representatives at the INEM school in Ciudad Jardín.